Prostaglandin E-2 production by high and low virulent strains of Paracoccidioides brasiliensis - Bordon, Ana Paula; Dias-Melicio, Luciane Alarcao; Acorci, Michele Janegitz; Biondo, Guilherme Augusto; Fecchio, Denise [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP] (Springer, 2007)
The production of prostaglandins (PGs) during fungal infections could be an important suppressor factor of host immune response. Host cells are one source of prostaglandin E-2 (PGE(2)); however another potential source of PGE(2) is the fungal pathogen itself. Thus, both host and fungal PGE2 production is theorized to play a role in pathogenesis, being critical for growth of the fungus and to modulate the host immune response. The purpose of this work was to investigate if high and low virulent strains of Paracoccidioides brasiliensis have the capacity to produce PGE(2) in vitro, and if this production was related to the fungal growth. The results demonstrated that both strains of P. brasiliensis produce high levels of PGE(2) and the treatment with indomethacin, a cyclooxygenase inhibitor, significantly reduced the production of this mediator, as well as the viability of the fungus. Thus, our data indicate that PGE(2) is produced by P. brasiliensis by a cyclooxygenase-dependent metabolic pathway, and its production is required for fungal survival. This discovery reveals an important factor that has potentially great implications for understanding the mechanisms of immune deviation during infection.
Keywords: prostaglandin E-2; Paracoccidioides brasiliensis; indomethacin; fungal growth